Fertility recovery of anther-derived haploid plants in Cape gooseberry (Physalis peruviana L.) - Francy Garcia-Arias; Erika Sánchez-Betancourt; Victor Núñez (Agronomía Colombiana, 2018)
The cape gooseberry (Physalis peruviana L.) is one of the most important Colombian exotic fruits. Chromosome doubling of anther-derived plants is a key factor in the application of double haploid technology for the genetic improvement of crops. In the present study, axillary buds from four haploid cape gooseberry genotypes were used to evaluate artificial chromosome doubling induced by colchicine and its effects on ploidy level and pollen fertility. Three concentrations of colchicine (5, 10 and 15 mM) and three exposure times (2, 4 and 6 h) were used to determine the best treatment for the generation of fertileB plants from axillary buds of haploid genotypes. The colchicine increased both the number of chromosomes, from 36 to 129, and the average chloroplasts in stomata guard cell, from 4.5 to 23.8. The optimal chromosome doubling of the haploids was obtained with the 5 mM colchicine solution and 2 h exposure time. This protocol produced chromosome doubling in over 60% of the regenerants of the four haploid genotypes, with a high level of fertility. Morphologically, the fertile mixoploid plants showed variation in the vegetative, flowering and fruit characteristics, as compared to the haploid plants.